Розробка дорожньої карти дослідницьких інфраструктур: досвід Швейцарії - Головащенко, О. С. (НДІ ПЗІР НАПрН України, 2022)
Наукова робота присвячена дослідженню правового забезпечення та практики розробки та прийняття Дорожньої карти дослідницьких інфраструктур на підставі аналізу досвіду Швейцарської Конфедерації. Зазначається, що дослідницькі інфраструктури сприяють досягненню вагомих результатів у фундаментальних наукових дослідженнях та розвитку передових технологій у Європейському дослідницькому просторі. Оскільки у Швейцарії триває підготовка Дорожньої карти дослідницьких інфраструктур на 2023 рік, метою якої є підготовка та визначення пріоритетів майбутніх і довгострокових інвестицій у дослідницькі інфраструктури, огляд нових проектів (включаючи суттєві оновлення існуючих) та оновлення інформації про проекти, представлених у попередніх Дорожніх картах, то зазначається, що процес складання Дорожньої карти дослідницьких інфраструктур Швейцарії проходить в декілька етапів. Звертається увага на те, що Дорожня карта дослідницьких інфраструктур Швейцарії не містить рішень щодо фінансування, натомість вона слугує інструментом стратегічного планування, детально описуючи довгострокові потреби в національних дослідницьких інфраструктурах та важливість участі Швейцарії в міжнародних інфраструктурних об’єктах і мережах. Водночас, у Швейцарії розбудова та підтримка дослідницької інфраструктури на національному рівні є обов’язком вищих навчальних закладів та науково-дослідних установ у межах Ради Швейцарських федеральних технологічних інститутів. На міжнародному рівні федеральний уряд країни будує та керує великомасштабними дослідницькими інфраструктурами у співпраці з іншими країнами (міжнародні інфраструктури). Problem setting. The research is devoted to the analysis of legal support and the practice of developing and adopting a road map of research infrastructures, based on the analysis of the experience of the Swiss Confederation. Analysis of resent researches and publications. Today, aspects of the development of innovation systems and research infrastructures of the European Union are a topic for research of many domestic researchers. At the same time, the analysis of the development of Roadmaps of research infrastructures of other countries, in particular, Switzerland remains relevant. Target of the research is to analyze the development of the Roadmap of research infrastructures of the Swiss Confederation. Article’s main body. Research infrastructures means a research facility necessary for conducting comprehensive research and development with high financial and technology demands, approved by the Government and established to be also used by other research organizations. Research Infrastructures are facilities, resources and services, including: major scientific equipment (or sets of instruments); knowledge-based resources such as collections, archives and scientific data; e-infrastructures, such as data and computing systems and communication networks. The Swiss Roadmap for Research Infrastructures is a planning tool for research infrastructures. SERI produces the Swiss Roadmap for Research Infrastructures every four years. At Swiss level, the 2023 Roadmap will present the new national infrastructure projects that Swiss cantonal universities and research institutes within the ETH Domain intend to build between 2025 and 2028. In addition, the report will include information on the status of the national infrastructure projects covered in the 2015 and 2019 editions. At international level, the 2023 Roadmap will show the international infrastructures that Switzerland is already involved in and which new participations are planned. Only projects that have successfully passed all three selection and review phases will appear on the Swiss Roadmap. The aim of this process is to select priority infrastructure projects. Conclusions and prospects for the development. The innovative development and the Roadmap of Swiss research infrastructures should be of significant interest to the Ukrainian scientific community. At the same time, an important step for Ukraine was the approval by the Cabinet of Ministers of the Concept of the State Targeted Program for the Development of Research Infrastructures in Ukraine for the period until 2026, as well as the approval of the Roadmap for the integration of the scientific and innovative system of Ukraine into the European Research Area.
Keywords: дослідницькі інфраструктури; Європейський дослідницький простір; науково-дослідна діяльність; Дорожня карта дослідницьких інфраструктур Швейцарської Конфедерації; research Infrastructures; European Research Area; research activity; Road Map of Research Infrastructures of the Swiss Confederation